2017
DOI: 10.1186/s40738-017-0033-1
|View full text |Cite
|
Sign up to set email alerts
|

“I am anxious and desperate”: psychological experiences of women with infertility in The Greater Accra Region, Ghana

Abstract: BackgroundResearch has shown that infertility affects millions of couples worldwide. Infertility is considered one of the most difficult life experiences and can result in psychological consequences for couples, especially for women. The purpose of this study was to explore the psychological experiences of women with infertility.MethodsA qualitative exploratory descriptive approach was used to conduct in-depth interviews. The psychological component of the bio-psychosocial model was used as a guiding framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 17 publications
(19 reference statements)
4
31
1
Order By: Relevance
“…As in other SSA countries [ 12 , 18 , 20 , 30 ], the lives of women with infertility in urban Gambia were marked by various kinds of economic, social and emotional problems. The concept of social suffering can be used to describe the impact of these various problems on women’s lives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in other SSA countries [ 12 , 18 , 20 , 30 ], the lives of women with infertility in urban Gambia were marked by various kinds of economic, social and emotional problems. The concept of social suffering can be used to describe the impact of these various problems on women’s lives.…”
Section: Discussionmentioning
confidence: 99%
“…When a marriage remains childless, some men abuse their wives, verbally or even physically [ 18 , 29 ]. Women expressed feelings of anxiety, frustration, grief, lack of self-esteem and a general sense of powerlessness [ 17 , 19 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…2017; Fledderjohann 2012; Tabong and Adongo 2013a), psychological distress (Alhassan, Ziblim, and Muntaka 2014; Anokye et al. 2017; Donkor, Naab, and Kussiwaah 2017; Fledderjohann 2012; Tabong and Adongo 2013b), reduced sexual satisfaction (Donkor, Naab, and Kussiwaah 2017; Nyarko and Amu 2015), relationship difficulties, marital instability and increased polygyny (Anokye et al. 2017; Fledderjohann 2012, 2017; Nyarko and Amu 2015; Tabong and Adongo 2013a; Wilkinson and Callister 2010), strained relationships with extended family members (Tabong and Adongo 2013a; Wilkinson and Callister 2010), and a loss of access to status and wealth (Tabong and Adongo 2013a; Alhassan, Ziblim, and Muntaka 2014).…”
Section: Introductionmentioning
confidence: 99%
“…When a marriage remains childless, some men abuse their wives, verbally, or even physically . Women expressed feelings of anxiety, frustration, grief, lack of self‐esteem, and a general sense of powerlessness …”
Section: Introductionmentioning
confidence: 99%
“…16,17 Women expressed feelings of anxiety, frustration, grief, lack of self-esteem, and a general sense of powerlessness. 18 In the qualitative research conducted by Boz and Okumus 19 indicated the relationship between the most significant aspect of the Perspect Psychiatr Care. 2019;55:328-335. wileyonlinelibrary.com/journal/ppc infertility experience and existentialist philosophy.…”
Section: Introductionmentioning
confidence: 99%